An ingested metallic wire migrating from stomach to pancreas treated by laparoscopic surgery: A case report - Hao, Fulong; Feng, Qingbo; Li, Jiaxin; Wu, Hong (Frontiers in Surgery, 2023)
Introduction: Foreign bodies inside the pancreas are rare and usually occur after the ingestion of sharp objects like fish bone, sewing needle and toothpick. An ingested metallic wire migrating from stomach to pancreas is very rare. Case Presentation: We report a 36-year-old woman who was admitted to our hospital with “3-day history of dull progressive epigastric pain”. Computed tomography of the abdomen revealed a linear, high-density body between the stomach wall and the pancreas. During the operation, a linear, hard, metallic wire was found in the adhesive tissue between the gastric antrum and the pancreatic body. The operation was uneventful and the patient recovered well. Conclusion: The case of foreign body inside the pancreas caused by a metallic wire is very rare. Radiological examinations play a vital role in the diagnosis of metallic wire ingestion. Metallic wire ingestion can be treated with laparoscopic surgery technically and safely.